Application of methodologies EPA, Mexican and IPCC for estimating biogas, a case study of the sanitary landfill Doña Juana, Bogota - Colombia - Urrego-Martínez, Elizarova; Rodríguez-Miranda, Juan Pablo (Universidad y Salud, 2016)
Objective: Compare the Mexican, EPA and IPCC methodologies for estimating biogas in a prediction horizon of 20 years applied in a case study in the landfill Doña Juana in Bogotá, Colombia. Materials and methods: A descriptive study for the development of prediction methodologies was carried out by examining the secondary information obtained from the initial data biogas production in the landfill, within a homogeneous phenomenon. Results: The average production of biogas (m3 / year) for Mexican, EPA and IPCC methods is 2.48E + 05, 2.14e + 05 and 6.71E + 05, respectively. The method with lower standard deviation and root mean square error is the Mexican. Conclusions: The application of the EPA, Mexican and IPCC models in the estimation of biogas in a landfill, believes that the trend of the first two exposed methods exhibit is decreasing exponentially, while the IPPC has exponentially growing trend, evaluated for a prediction period of 20 years. With the determination of the amount of biogas by different methodologies, the possibility of exposure of risk in the long term with adverse effects on public health of the adjacent community landfills is reduced.